Stabilization of heavy metals in a marine clay matrix - Easton Vee-Foong Christopher Laval (2008)
This project aims to study the possibility of using marina clay as a matrix to stabilize heavy metals present in spent fluid catalytic cracking (FCC) catalyst, namely vanadium and nickel to produce ceramic construction materials.